2021
DOI: 10.3390/life11020155
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potentials of Syzygium fruticosum Fruit (Seed) Reflected into an Array of Pharmacological Assays and Prospective Receptors-Mediated Pathways

Abstract: Syzygium fruticosum (SF), a valuable Bangladeshi fruit, is considered an alternative therapeutic agent. Mainly, seeds are used as nutritional phytotherapy to ease physical and mental status by preventing chronic diseases. Here, we scrutinized theS. fruticosum seed’s fundamental importance in traditional medicine by following an integrated approach combining in vivo, in vitro,and in silico studies. The SF was fractionated with different solvents, and the ethyl acetate fraction of SF (EaF-SF) was further studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Tian et al [ 84 ] reported that IDD was associated with upregulation of cGAS, STING, and NLRP3; moreover, pigallocatechin-3-gallate inhibited the cGAS/STING/NLRP3 pathway and exerted antiapoptotic and anti-inflammatory effects. Gallic acid is a natural phenolic (a secondary metabolite of grape seeds, Syzygium fruticosum fruit, and other plants [ 85 ]). Gallic acid exerts strong antioxidant and anti-inflammatory effects [ 86 ].…”
Section: Natural Pharmacological Productsmentioning
confidence: 99%
“…Tian et al [ 84 ] reported that IDD was associated with upregulation of cGAS, STING, and NLRP3; moreover, pigallocatechin-3-gallate inhibited the cGAS/STING/NLRP3 pathway and exerted antiapoptotic and anti-inflammatory effects. Gallic acid is a natural phenolic (a secondary metabolite of grape seeds, Syzygium fruticosum fruit, and other plants [ 85 ]). Gallic acid exerts strong antioxidant and anti-inflammatory effects [ 86 ].…”
Section: Natural Pharmacological Productsmentioning
confidence: 99%
“…Plants with medicinal properties are being used in health care since the dawn of civilization (Khan et al, 2020;Moni et al, 2021;Rahman et al, 2021;Sofowora et al, 2013). Globally, many studies have been conducted to check their effectiveness, with some of the results leading to plant-based medicines (Goni et al, 2021;Hossen et al, 2021;Sofowora et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the predominant mental disorders approximately 10% of people worldwide have depression ( Organization, 2017 ). Several studies have reported that stress is also a causative factor for anxiety and depression, leading to the increased formation of free radicals and initiating oxidative stress ( Bellah et al., 2017 ; Hossain et al., 2020 ; Hossen et al., 2021a ; Moni et al., 2021 ; Nirmal et al., 2008 ). Despite this, various types of medicine, such as tricyclic antidepressants, monoamine oxidase inhibitors, and selective serotonin reuptake inhibitors, are the most commonly used drugs for anxiety and depression management ( Belmaker and Agam, 2008 ; Tareq et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%